RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI DAN AKADEMIK SANTRI DENGAN METODE PROTOTYPE - Devinka Putri; Riki Afriansyah; Putri Armilia Prayesy (STMIK KHARISMA Makassar, 2026)
The management of administrative and academic activities in Islamic boarding schools (pesantren) is an essential aspect in supporting the quality of educational services. However, manual processes often create obstacles such as delays in data processing, information duplication, and inefficiency in service delivery. Based on these issues, this study focuses on developing a Web-Based Santri Administrative and Academic Information System as a means to improve the effectiveness, accuracy, and transparency of data management in pesantren. The development process applies the prototype method, which allows users to be directly involved in the system design and evaluation stages. The system includes integrated management of student, teacher, class, grade, and financial administration data. Testing was conducted using black-box testing and User Acceptance Testing (UAT) to verify system functionality and user satisfaction levels. The results show that all system features performed well, achieving a feasibility rate of 90.06%, categorized as highly feasible. Therefore, this system serves as an effective solution to support the digitalization of administrative and academic processes within Islamic boarding schools.